A qualitative exploration of how a community engagement approach influences community and health worker perceptions related to family planning service delivery in Togo - Dougherty, Leanne; Kassegne, Sethson; Nagbe, Robert; Babogou, Joseph; Peace, Paula; Moussa, Farida; Kirk, Karen; Tokplo, Hilaire; Ouro-Gnao, Djibril; Agbodjan, Serge Prince; Loll, Dana; Werwie, Timothy R.; et al. (Frontiers in Reproductive Health, 2024)
Background There is a growing body of evidence that asserts community engagement approaches can improve the quality of reproductive health services. Family planning (FP) programs in Togo are implementing such approaches, which aim to mobilize both health workers and communities to improve FP service quality and FP uptake. However, there is not enough known about the enabling factors and challenges associated with implementation, or the extent to which the programs improve outcomes leading to contraceptive uptake. Methods We qualitatively explored how a community engagement approach influenced health worker and community perceptions related to FP service delivery in and around the city of Lomé, Togo, within the context of the broader integration of social and behavior change and service delivery. We conducted 18 in-depth interviews with health workers and 9 focus group discussions with community members. Results We found the approach, which included community dialogues, site walkthrough visits and the development of community action plans, worked synergistically together to support collaborative action between communities and health workers to increase mutual understanding of their collective needs related to FP services. Community members cited improved reception at the health facilities by health workers and indicated that the site walkthrough visits created a greater sense of empathy towards the providers and the challenges faced in their work environment. Health workers acknowledged a greater understanding of barriers at the community level following community dialogues, particularly among community members that are not routinely encountered at the health facility for reproductive health services such as men and youth. We found limited implementation of health facility improvements included in community action plans because they were dependent on commitment from community leadership and the need to mobilize additional support or financial resources. Conclusion Community engagement approaches are a promising mechanism to support collaboration and enhance mutual understanding between health workers and communities to achieve improved FP service quality. Future programs should consider incorporating additional mechanisms to monitor community action plans and provide support to address structural challenges at the facility level particularly those that require financial resources.